Early outcomes of on-pump versus off-pump coronary artery bypass grafting - Hussain, Ghulam (Pak J Med Sci, 2016)
OBJECTIVES: To see the early post-operative outcomes of off-pump versus on-pump coronary artery bypass graft surgery. METHODS: This retrospective analytical study was conducted at Ch. Pervaiz Elahi Institute of Cardiology Multan, Pakistan. Our Primary outcome variables were; necessity of inotropic support, nonfatal myocardial infarction, ICU stay, nonfatal stroke, new renal failure requiring dialysis and death within 30 days after operation. There were two groups of patients; Group-I (On-pump group) and Group-II (Off-pump Group). SPSS V17 was used for data analysis. Independent sample t-test and Mann Whitney U test were used to compare quantitative Variables. Chi-square test and Fisher’s exact test were used to analyze qualitative variables. P-value ≤ 0.05 was considered significant. RESULTS: Three hundred patients were included in this study. There were no significant difference regarding risk factors except hyper-cholestrolemia which was high in off pump group (p-value 0.05). Angiographic and Echocardiographic characteristics e.g. preoperative ejection fraction, LV function grade and severity of CAD was same between the groups. Mortality risk scores and Priority status for surgery were also same. Regarding post-operative outcomes; Post-op CKMB Levels, need and duration of inotropic support, mechanical ventilation time and ICU stay was significantly less in Off-Pump group (p-value 0.001, <0.0001, 0.006, 0.025 and 0.001 resp.). Peri-operative chest drainage was significantly high in On-pump CABG group (p-value 0.027). Incidence of post-op complications was not statistically different between the groups. CONCLUSIONS: At 30 days follow-up, Incidence of myocardial infarction, necessity and duration of inotropic support, ICU stay period and peri-operative bleeding were significantly less in off-pump group. The incidence of neurologic, pulmonary and renal complications was same between the off-pump and on-pump groups.